PENGARUH PENERIMAAN PAJAK DALAM NEGERI, PEMBENTUKAN MODAL BRUTO, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Perwira, Abi Revyansah (Jurnal Analisis Bisnis Ekonomi, 2019)
The purpose of this study is to examine and analyze the effect of domestic tax revenues, gross capital formation, and inflation on economic growth. Many theories say that economic growth depends on government spending from the fiscal side, investment for gross capital formation, and inflation from the monetary side. However, government spending as a stimulus in the real sector relies heavily on tax revenues as the main source of financing, especially income tax and VAT where both types of taxes are the biggest contributors to domestic tax revenues. Whereas gross capital formation can create employment and increase production of goods and services. Inflation can lead to a decrease in public consumption which impacts on reducing the production of goods and services, which hampers economic growth. The data in the study are time-series secondary data obtained from BPS-Statistics Indonesia and World Bank during the period 1991 – 2017. The analytical method used is a multiple log-linear regression model. According to the results of the analysis, it could be concluded that domestic tax revenues and gross capital formation have a positively significant influence on economic growth, while inflation has a negatively significant influence.